Implementación del control interno bajo riesgo en el Gad parroquial de Toacaso, provincia de Cotopaxi, cantón Latacunga, en el periodo marzo 2019 – agosto 2019. - Farinango Catota, Edwin Patricio. (2019)
The Decentralized Autonomous Government of Toacaso Parish, as an institutional policy, carries out the necessary management to provide itself with administrative tools, materials, and human personnel that allow optimizing and strengthening its institutionality. By a previous analysis, the inefficient control in the administrative-financial management was identified, which prevents necessary information from being provided to maintain an adequate development process, so it is intended to be corrected through an internal control system, which provides its leaders with a tool where the policies, procedures, and standards that regulate and direct all the activities of the staff are clearly exposed to fulfill their objectives and goals; in this project, the implementation has been proposed by an applicable internal control system, practical and based on current legal regulations. Consequently, information collection instruments such as the interview and the observation form have been used, in addition to the bibliographic and field research which allowed diagnosing the financial area of the parish and proposing an internal control system. The project contains, in the first instance, a description of the general aspects of the Parish Government of Toacaso, its location, population, organizational structure, vision, mission, and objectives. Next, the concepts about the subject to be discussed are described, as well as some laws and regulations that intervene for the application of internal control in Parish Governments, aimed at minimizing risk, so the COSO II model was used. The diagnosis of the current situation of the activities carried out within the financial area was made through a comparative analysis with the current Internal Control Standards.